Winning and losing on the Western Front the British Third Army and the defeat of Germany in 1918 - Boff, Jonathan (Cambridge military histories, 2012)
The 'Hundred Days' campaign of 1918 remains a neglected aspect of the First World War. This revealing insight into the crucial final months of the First World War uses state-of-the-art methodology to present a rounded case study of the ability of both armies to adapt to the changing realities they faced.